Effect of Leadership Style, Reward and Punishment and Compensation Against Employee Motivation - M. Raka Mahendra; Faroman Syarief (DINASTI RESEARCH, 2022)
Article Literature Review of the Effects of Leadership Style, Reward and Punishment and Compensation on Employee Motivation is a scientific article that aims to build a research hypothesis on the influence of variables to be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other online academic media. The results of this article are that: 1) Leadership Style influences Employee Motivation; 2) Reward and Punishment affect Employee Motivation; and 3) Compensation has an effect on Employee Motivation. Apart from these 3 exogenous variables that affect the endogenous variable Employee Motivation there are many other factors including Competency, Performance Assessment and Work Culture.